COGNITION AND FRAILTY IN COMMUNITY-DWELLING ELDERLY - Renata Rabelo Pereira; Cleane Rosa Ribeiro da Silva; Selene Cordeiro Vasconcelos; Lucineide Alves Vieira Braga; Edilene Araújo Monteiro; Maria de Lourdes de Farias Pontes (Universidade Federal do Paraná, 2019)
Objective: To analyze the relationship between cognitive performance and frailty in community-dwelling elderly.Method: Cross-sectional, observational and quantitative study conducted in August-December 2016, with 126 elderly registered in a Family Health Unit of João Pessoa, state of Paraíba. Mini Mental State Examination (MMSE) was used for cognitive assessment and the Edmonton Frailty Scale was used for the assessment for frailty. Descriptive and inferential analysis were performed, and Pearson's chi-square test of independence, Nonparametric Spearman and Kendall tests and Cramér's V Coefficient and Odds Ratio (OR) tests were applied.Results: The cognitive performance assessment revealed that 24 (19%) elderly had cognitive impairment and 50 (39.6%) were frail. Elderly people with cognitive impairment were 2.56 (95% CI: 0.55-0.96) more likely to be frail.Conclusion: There was a statistically significant relationship between cognitive performance and frailty among community-dwelling elderly, demonstrating that older people with cognitive impairment are more likely to be frail.